The rational application of points of interest data in the evaluation of public toilets population coverage in China - Junxia Miao; Fanglei Zhong; Luyao Ying; Chunlin Huang; Feng Gao; Xiaoyu Song (International Journal of Digital Earth)
Sanitation facilities are essential human rights that contribute to quality of life and the realization of other rights, as demonstrated by the population coverage of public toilets. Traditional data sources lack spatial information, limiting research on public toilet coverage. Point of interest (POI) data addresses this gap, clarifying the spatial distribution of public toilets across functional areas. This data allows for assessments at provincial levels or even more granular spatial scales, serving as a valuable supplement to existing datasets. This study integrates statistical data, POI data, and geospatial information to construct a public toilet population coverage assessment model based on POI data. The findings reveal a substantial increase in the number, construction density, and population coverage of public toilets in China, with the urban public toilet construction density meeting the minimum standard threshold by 2020. Nonetheless, significant regional disparities persist at the provincial level, with the eastern and western regions exhibiting pronounced imbalances. These disparities are attributed primarily to fewer policy directives and limited environmental funding in the western region. Moreover, the spatial distribution patterns of public toilets in terms of number and density derived from POI data align closely with those obtained from statistical data.